2019
DOI: 10.3390/healthcare7030084
|View full text |Cite
|
Sign up to set email alerts
|

Power and Design Issues in Crossover-Based N-Of-1 Clinical Trials with Fixed Data Collection Periods

Abstract: “N-of-1,” or single subject, clinical trials seek to determine if an intervention strategy is more efficacious for an individual than an alternative based on an objective, empirical, and controlled study. The design of such trials is typically rooted in a simple crossover strategy with multiple intervention response evaluation periods. The effect of serial correlation between measurements, the number of evaluation periods, the use of washout periods, heteroscedasticity (i.e., unequal variances among responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As vascular malformations are rare and heterogenous, the use of a CDR design offers the opportunity to generate interpretable data on e cacy and safety by analyzing each patient as their own control. We consider this design to be suited to investigate the e cacy of new treatments in those rare diseases, for which randomized clinical trials are less feasible due to the low numbers of patients affected and double blind randomized repeated rechallenges (as implemented in 'n = 1' trials) are not possible due to carry-over effects (34).…”
Section: Discussionmentioning
confidence: 99%
“…As vascular malformations are rare and heterogenous, the use of a CDR design offers the opportunity to generate interpretable data on e cacy and safety by analyzing each patient as their own control. We consider this design to be suited to investigate the e cacy of new treatments in those rare diseases, for which randomized clinical trials are less feasible due to the low numbers of patients affected and double blind randomized repeated rechallenges (as implemented in 'n = 1' trials) are not possible due to carry-over effects (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles in this Special Issue discuss important statistical issues. Wang and Schork [ 9 ] used analytical and simulation studies to look at the effect of serial correlation, number of periods/phases, the presence of washout periods, and heteroscedasticity on statistical power in non-randomised AB (or further permutations) alternation designs (where ‘A’ is baseline and ‘B’ is treatment). They showed that the power to detect an effect of the intervention decreased as the strength of serial correlation increased across all the alternation designs they tested.…”
Section: Exploring Statistical Issuesmentioning
confidence: 99%
“…Other than Rochon (1990), all of the authors reviewed in Section 1 considered power for their proposed methods, but only for specified sample sizes and/or effect sizes (McKnight et al, 2000;Borckardt et al, 2008;Lin et al, 2016). Wang & Schork (2019) followed up on Rochon's work, investigating power, but only considered trials with 𝑚 = 400. None of the aforementioned authors gave guidance on how to compute sample sizes.…”
Section: Sample Size Considerations When Planning N-of-1 Trialsmentioning
confidence: 99%